The Impact of Tax Forms on Economic Growth - Evidence from Serbia - Kalaš, Branimir; Milenković, Ivan; Pjanić, Miloš; Andrašić, Jelena; Milenković, Nada (Industrija, 2017)
The aim of the paper is to show the relevance of nexus between tax forms and economic growth and how they affect on gross domestic product in Serbia for the period 2006-2015. The impact is manifested through the analysis of three main tax forms: personal income tax (PIT), corporate income tax (CIT) and value-added tax (VAT) and their effect on the macroeconomic indicator as gross domestic product (GDP). The analysis is for a period of ten years in Serbia, where the regression model is constructed so that the GDP is defined as the dependent variable, while the tax forms are set as independent variables. To ensure correctly specified regression model, authors used the next test: VIF test, BP and BPG test, as well as Ramsey reset test. Results show a high degree of positive correlation between the observed variables and the positive impact of the personal income tax, corporate income tax and value-added tax on the gross domestic product, but it is only the impact of value added tax statistically significant.
Keywords: Economic Growth; Income; Tax